2018
DOI: 10.1016/j.lfs.2017.10.039
|View full text |Cite
|
Sign up to set email alerts
|

Caffeine and acetaminophen association: Effects on mitochondrial bioenergetics

Abstract: We suggest that the antioxidant effects of caffeine and/or its interactions with mitochondrial bioenergetics may be involved in its beneficial effects against APAP hepatotoxicity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 45 publications
0
11
0
Order By: Relevance
“…Mitochondrial function can be affected by pesticide exposure, tobacco use or caffeine consumption. 10,22,23,44 We, among others, have reported that caffeinated soda intake was associated with earlier AAO 5 or increased PD risk. 45 Hence, caffeinated soda appears to be different from other caffeinated beverages and potentially caffeine-independent mechanisms are driving these effects.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Mitochondrial function can be affected by pesticide exposure, tobacco use or caffeine consumption. 10,22,23,44 We, among others, have reported that caffeinated soda intake was associated with earlier AAO 5 or increased PD risk. 45 Hence, caffeinated soda appears to be different from other caffeinated beverages and potentially caffeine-independent mechanisms are driving these effects.…”
Section: Discussionmentioning
confidence: 94%
“…For example, pesticide exposure can produce reactive oxygen species (ROS) by redox cycling, inducing mtDNA damage. 10 In addition, smoking and vaping have been shown to be associated with mitochondrial gene dysregulation 21 and there is evidence that caffeine affects mitochondrial bioenergetics 22 and increases mitochondrial function. 23 Our study aimed to analyze these interactions between the MGS and lifestyle and environment in LRRK2 -PD and iPD.…”
Section: Introductionmentioning
confidence: 99%
“…Mitochondrial function can be affected by tobacco use, caffeine consumption, or pesticide exposure. 10,[21][22][23] We, among others, have reported that caffeinated soda intake was associated with earlier AAO 5 or increased PD risk. 47 Hence, caffeinated soda appears to be different from other caffeinated beverages and potentially caffeine-independent mechanisms are driving these effects.…”
Section: G S I S a S S O C I A T E D W I T Hmentioning
confidence: 91%
“…Mitochondrial function can be affected by tobacco use, caffeine consumption, or pesticide exposure. 10,[21][22][23] Smoking and vaping have been shown to be associated with mitochondrial gene dysregulation 24 and there is evidence that caffeine affects mitochondrial bioenergetics 22 and increases mitochondrial function. 23 Pesticides like rotenone or paraquat are known to increase mitochondrial dysfunction by inducing redox cycling or binding to complex I, which both result in the production of ROS.…”
mentioning
confidence: 99%
“…While scarce, a few studies have examined the role of components which could influence hepatotoxicity of some of these drugs. Caffeine has been shown to influence APAP-induced liver injury by improving mitochondrial function [193], though it was given 30 minutes prior to APAP treatment, and hence it is unclear if influence on APAP metabolism played a role in the observed protection. Early studies on acute ethanol administration before APAP overdose showed a preventive effect of ethanol on APAP-induced hepatotoxicity due to interference with APAP metabolism [194], though additional mechanisms influencing mitochondrial transport of NADPH are also suggested [195].…”
Section: Additional Factors Influencing Effects Of Drugs On Mitochmentioning
confidence: 99%